Global border restrictions in 2020–2021: Adherence and the effectiveness in long-term COVID-19 epidemic control. Issue 52 (March 2023) - Li, Zhiyao; Yang, Boran; Wang, Jiale; Wen, Yanchao; Xu, Jianguo; Ling, Li; Wang, Tong
Abstract: Background: Restrictions on international travel were widely applied to contain cross-border COVID-19 diffusion, while such applications varied globally, and little was known about their impacts on the long-term epidemic progression. Methods: We explored the global diversity in maintaining border policies classified to four levels (screening, quarantine, ban on regions and total border closure) using data of 185 countries and regions between 01 January 2020 to 31 December 2021. By using Ordinary least squares (OLS) regression and quantile regression (QR) models, we examined the relationship between total COVID-19 incidence and the cumulative duration of each policy level in 2020–2021, and the heterogeneity of such association across different transmission severity countries. Results: Firstly, "ban on regions" was the most durable policy applied in high-income countries, while in low-income countries, less stringent measures of screening and quarantine arrivals were applied the longest. Secondly, the cumulatively longer maintenance of the border quarantine was significantly associated with lower infections (log) in COVID-19 high-prevalent countries (75th QR, coefficient estimates [ β ] = −0.0038, 95% confidence interval: −0.0066 to −0.0010). By contrast, in medium and high transmission severity countries, those with longer duration of imposing bans on regions showed no suppressing effects but significantly higher COVID-19 incidence (OLS regression, β  = 0.0028, 95% CI: 0.0009–0.0047; 75th QR, β  = 0.0039, 95% CI: 0.0014–0.0063). No other significant results were found. Conclusion: From the long-term perspective, inbound quarantine was effective in mitigating severe epidemics. However, in countries with medium or high COVID-19 prevalence, our findings of ban on regions highlighted its ineffectiveness in the long-term epidemic progression. Highlights: There were large disparities between countries in the application and maintenance of border polices against COVID-19. We examined and compared the impact of four border restrictions on suppressing long-term epidemics with real-world evidence. Maintaining border quarantine could be prudent for countries with severe epidemics. Long-lasting implementation of bans on high-risk foreign regions may contribute limitedly to the epidemic control.